2013
DOI: 10.1007/jhep04(2013)130
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field-induced gluonic (inverse) catalysis and pressure (an)isotropy in QCD

Abstract: Abstract:We study the influence of strong external magnetic fields on gluonic and fermionic observables in the QCD vacuum at zero and nonzero temperatures, via lattice simulations with N f = 1+1+1 staggered quarks of physical masses. The gluonic action density is found to undergo magnetic catalysis at low temperatures and inverse magnetic catalysis near and above the transition temperature, similar to the quark condensate. Moreover, the gluonic action develops an anisotropy: the chromo-magnetic field parallel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
213
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(245 citation statements)
references
References 91 publications
(180 reference statements)
31
213
1
Order By: Relevance
“…The magnetic susceptibility C r 2 is positive for temperatures above the transition, which means that the quark-gluon plasma exhibits a paramagnetic behavior to lowest (linear) order in the magnetic field. Paramagnetism in the quarkgluon plasma has been also previously found in other lattice studies [7,9].…”
Section: Results and Conclusionsupporting
confidence: 80%
“…The magnetic susceptibility C r 2 is positive for temperatures above the transition, which means that the quark-gluon plasma exhibits a paramagnetic behavior to lowest (linear) order in the magnetic field. Paramagnetism in the quarkgluon plasma has been also previously found in other lattice studies [7,9].…”
Section: Results and Conclusionsupporting
confidence: 80%
“…We also tested stochastic wall sources to obtain Π(0) as the second moment of a momentum projected current-current correlation function and found that it can compete with the accuracy of the homogeneous susceptibility for a sufficiently large number of random sources. It is interesting to note that 0 can also be obtained via stochastic wall sources at finite temperatures, giving direct access to the renormalized magnetic susceptibility 0 ( ) − 0 ( = 0) that enters the QCD equation of state at finite magnetic fields [48,55,56,58,71,72] . FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The only divergences that do not cancel in the difference ∆ f are the B−dependent ones and it can be show that such divergences are temperature independent (see e.g. [7,8]). Motivated by this result and by the physical observation that we are interested in the magnetic properties of the thermal medium and not in those of the…”
Section: The Methodsmentioning
confidence: 99%